Perencanaan dan evaluasi kesehatan / Suhadi ; editor, Muh. Kardi Rais, Haeruddin, Muh. Ryman Napirah - SUHADI, 1977-; Muh Kardi Rais; Haeruddin; Muh. Ryman Napirah (Leutikaprio, 2015)
x, 330 hlm. : ilus. ; 19 cm